Illuminating the Middle Ages
1 online resource.
Keywords: The twenty-eight essays in this collection showcase cutting-edge research in manuscript studies, encompassing material from late antiquity to the Renaissance. The volume celebrates the exceptional contribution of John Lowden to the study of medieval books. The authors explore some of the themes and questions raised in John’s work, tackling issues of meaning, making, patronage, the book as an object, relationships between text and image, and the transmission of ideas. They combine John’s commitment to the close scrutiny of manuscripts with an interrogation of what the books meant in their own time and what they mean to us now.